2019
DOI: 10.1155/2019/1709718
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Activates the Protective Effects of the AMPK Pathway in Acute Lung Injury Caused by Paraquat Poisoning

Abstract: Objective To observe whether metformin (MET) plays a protective role in acute lung injury (ALI) induced by paraquat (PQ) poisoning in rats by activating the AMPK/NF-κB signaling pathway. Methods PQ exposure was used to construct a rat model of ALI and a model of acute type II alveolar epithelial cell (RLE-6TN) injury, and MET intervention was performed. Rat lung tissue samples were collected to evaluate pathological changes in rat lung tissue, the oxidation index, and inflammatory factors; cell viability was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 33 publications
(35 reference statements)
2
25
0
Order By: Relevance
“…Studies have shown that metformin alleviates inflammation and protects against acute lung injuries in several animal models. First, metformin treatment significantly reduces lipopolysaccharide (LPS)-induced lung destruction and paraquat poisoning-induced acute lung injury (42)(43)(44)(45). Second, metformin attenuates lung injury caused by the high pressure of mechanical ventilation (46).…”
Section: Figure 2 |mentioning
confidence: 99%
“…Studies have shown that metformin alleviates inflammation and protects against acute lung injuries in several animal models. First, metformin treatment significantly reduces lipopolysaccharide (LPS)-induced lung destruction and paraquat poisoning-induced acute lung injury (42)(43)(44)(45). Second, metformin attenuates lung injury caused by the high pressure of mechanical ventilation (46).…”
Section: Figure 2 |mentioning
confidence: 99%
“…Animal models are frequently used in basic researches to study the function of drugs or molecules, and rats are frequently used as models of PQ‐induced lung injury 21,22 . Besides, type II rat alveolar epithelial cells (RLE‐6TN) are frequently used for in vitro studies in the toxicity of PQ 23,24 . Compared to the type I alveolar cell, type II cell has the potential of division, proliferation and differentiation into type I cells, and they can repair the damaged epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Besides, type II rat alveolar epithelial cells (RLE-6TN) are frequently used for in vitro studies in the toxicity of PQ. 23,24 Compared to the type I alveolar cell, type II cell has the potential of division, proliferation and differentiation into type I cells, and they can repair the damaged epithelium. Damage of type II alveolar cells may reduce the surfactant on alveoli, leading to lung oedema and respiratory distress, which is concert with the features of PQ-induced rats.…”
mentioning
confidence: 99%
“…However, it is lethal to human and animals when ingested orally and there are still no effective and specific antidotes for PQ. Patients with acute PQ poisoning usually died within several days to weeks after confirmed exposure due to hypoxemia or multiple organs failure, which causes a considerable economic burden and increased medical resource use for families and countries [3][4][5][6]. Therefore, for patients, especially in critically ill patients, clinical outcome evaluation and risk assessment in a timely manner is crucial and essential for medical resources using wisely, which has become a public health problem concerned by doctors and patients, as well as social security agency.…”
Section: Introductionmentioning
confidence: 99%